Validitas Lembar Kerja Peserta Didik (LKPD) Berbasis Model Problem Based Learning (PBL) Pada Materi Sistem Peredaran Darah Kelas XI SMA - Resi Maimufi; M Haviz; Rina Delfita; Najmiatul Fajar (Edusainstika: Jurnal Pembelajaran MIPA, 2021)
This research is motivated by the problem of the lack of teaching materials used in learning, in the learning process only using textbooks as a learning resource and there are still no learning resources that can solve student problems. The purpose of this study was to produce a valid student worksheet based on the Problem Based Learning (PBL) model on the Circulatory System Material for Class XI at SMAN 2 Pulau Punjung, Dharmasraya Regency. This research is a development research using a 4-D development model. The instruments used in this study were the validity test sheet and the interview sheet. Data analysis using descriptive analysis. Based on the results of the data analysis carried out, it can be concluded that: The results of the study show that LKPD based on Problem Based Learning (PBL) is very valid in learning on the circulatory system material for class XI at SMAN 2 Pulau Punjung, Dharmasraya district with a percentage of 91.90%.